2012
DOI: 10.1007/s11664-012-2013-x
|View full text |Cite
|
Sign up to set email alerts
|

Post-growth Annealing of Cadmium Zinc Telluride Crystals for Room-Temperature Radiation Detectors

Abstract: We investigated the effects of post-growth annealing on cadmium zinc telluride crystals intended for use as room-temperature radiation detectors. Annealing under Cd vapor effectively eliminated Te inclusions. The material's resistivity was lowered, and loss of Zn component was observed. Annealing under Cd + Zn vapors similarly removed Te inclusions. Furthermore, after exposure to the two vapors, we noted a change in the crystal surface morphology, i.e., formation of patterns of parallel lines. In contrast to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…This procedure also reduces the material's resistivity. Reportedly, annealing in a combination of Cd-rich and Zn-rich atmospheres maintains high resistivity [11]. The second thermal-annealing approach involves inducing movement of the Te inclusions under temperature gradients and their accumulation at the sample's high-temperature side, leaving the higher-quality regions of the crystal with fewer smaller particles.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure also reduces the material's resistivity. Reportedly, annealing in a combination of Cd-rich and Zn-rich atmospheres maintains high resistivity [11]. The second thermal-annealing approach involves inducing movement of the Te inclusions under temperature gradients and their accumulation at the sample's high-temperature side, leaving the higher-quality regions of the crystal with fewer smaller particles.…”
Section: Introductionmentioning
confidence: 99%
“…This is close to a reduction of one order of magnitude in the resistivity. In CdZnTe annealed at 670 C for 50 hours in Cd vapor, it was reported that the resistivity of the material was reduced up to five orders of magnitude [15]. The reasons for these observations are changes caused by the annealing processes to the concentrations of deep-level Te anti-sites, Cd interstitials, and Cd vacancies, that are responsible for the high resistivity of CdZnTe [15]- [17], and in CdMnTe.…”
Section: Resultsmentioning
confidence: 99%
“…In CdZnTe annealed at 670 C for 50 hours in Cd vapor, it was reported that the resistivity of the material was reduced up to five orders of magnitude [15]. The reasons for these observations are changes caused by the annealing processes to the concentrations of deep-level Te anti-sites, Cd interstitials, and Cd vacancies, that are responsible for the high resistivity of CdZnTe [15]- [17], and in CdMnTe. For CdZnTe annealed in Cd vapor, it was suggested by Yang et al [13] that the electrical compensation was lost due to extra Cd interstitials from the Cd vapor, thus resulting in shifting of the Fermi level towards the bottom of the conduction band.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the resistivity of CZT decreases with an increase in the dislocations. Yang et al [12] conducted thermal annealing under Zn-vapor after Cd-vapor annealing to determine the specific resistivity of CZT. Egarievwe et al [10] analyzed the thermal annealing conditions required to remove and reduce Te inclusions; they reported that long-term thermal annealing at a low temperature of 783 K is more effective in reducing thermal stresses and irregular Cd inclusions than short-term thermal annealing at a high temperature of ∼1,170 K.…”
Section: Introductionmentioning
confidence: 99%